Effect of directly observed oral iron supplementation during pregnancy on iron status in a rural population in Haryana: A randomized controlled trial - Farhad Ahamed; Kapil Yadav; Shashi Kant; Renu Saxena; Mohan Bairwa; Chandrakant S Pandav (Wolters Kluwer Medknow Publications, 2018)
Background: In India, more than half of the pregnant women suffer from anemia. Low compliance to iron supplementation is one of the important reasons. Objectives: The objective of the study is to estimate the reduction in the prevalence of anemia, improvement in iron status, and to compare the compliance to oral iron supplementation during pregnancy between directly observed iron-folic acid (IFA) supplementation group and control group. Methods: This was a community-based open labeled parallel block-randomized controlled trial including 400 pregnant women in a rural setting of north India. In the intervention group, the first dose of IFA every week was supervised by ASHA and women were instructed to take the remaining tablets during the week as per the prescription. In control group, IFA tablets were supplemented without direct supervision. Results: After 100 days of IFA supplementation, the reduction in anemia in the intervention group was 6% higher as compared to control group (P = 0.219). The increase in the mean hemoglobin level over and above control group was 0.52 g/dl in intervention group (P < 0.001). However, the mean increase in serum ferritin level in the intervention group was similar to the control group. The mean percentage compliance in the intervention group was almost 9% higher than that of control group (P = 0.001). Conclusion: Directly supervised oral iron (IFA) supplementation improves compliance to oral iron (IFA) supplementation and also improves hemoglobin status among pregnant women. However, the mean increase in serum ferritin and reduction in the prevalence of anemia in the intervention group were not higher than the control group.